Perspectives in business informatics research : 14th International Conference, BIR 2015, Tartu, Estonia, August 26-28, 2015, Proceedings /: 14th International Conference, BIR 2015, Tartu, Estonia, August 26-28, 2015, Proceedings. (2015) - Unknown
No abstract available